The Effect of Boiled Mung Bean Seeds on Alanine Aminotransferase Levels in Rats (Rattus norvegicus L.) Induced by NaNO2 - nabila dwi ayu pratiwi; Hartalina Mufidah; Ahdiah Imroatul Muflihah; Wima Anggitasari (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2024)
Background: Sodium nitrite is a chemical compound used in the coloring and preserving process of processed meat. Excess sodium nitrite entering the body can have clinical impacts on health, especially the liver. Disorders of the liver can be identified by increased levels of Alanine Aminotransferase. Mung beans contain antioxidants, a compound that has benefits as a hepatoprotection. Purpose: This study aims to determine the effect of Mung bean stew on Alanine aminotransferase levels in rats (Rattus norvegicus L.) with anemia before and after administration. Method: This research design is an experimental study with quantitative data collection. This study was conducted in June–July 2024. The sample in this study was rats (Rattus norvegicus), which were taken randomly using random sampling techniques. The Mung beans used in this study were Mung beans that had undergone an infusion process. After collecting data, the researcher processed the data using Paired sample-t test analysis, One-Way ANOVA, and Post Hoc Tukey using SPSS. Results: The Paired sample-t test for Alanine Aminotransferase levels in rats (Rattus norvegicus) with anemia showed sig>0.05 in all treatment groups. The test results of the average change in Alanine Aminotransferase levels before and after between groups showed a sig value <0.05. Conclusion: Based on this study, it can be concluded that Based on this research, it can be concluded that there is no effect of boiled Mung beans on Alanine aminotransferase levels.